2022
DOI: 10.3390/ijms232415869
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl Cysteine-Mediated Improvements in Dental Restorative Material Biocompatibility

Takanori Matsuura,
Keiji Komatsu,
Takahiro Ogawa

Abstract: The fibroblast-rich gingival tissue is usually in contact with or adjacent to cytotoxic polymer-based dental restoration materials. The objective of this study was to determine whether the antioxidant amino acid, N-acetyl cysteine (NAC), reduces the toxicity of dental restorative materials. Human oral fibroblasts were cultured with bis-acrylic, flowable composite, bulk-fill composite, self-curing acrylic, and titanium alloy test specimens. Cellular behavior and function were analyzed on and around the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Polymerization initiators such as benzoyl peroxide (BPO) and camphorquinone (CQ) compromise cell viability [ 47 , 59 , 60 , 61 ]. BPO, a major initiator for self-curing acrylic resin, is broken down during polymerization to release radicals that injure surrounding cells [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerization initiators such as benzoyl peroxide (BPO) and camphorquinone (CQ) compromise cell viability [ 47 , 59 , 60 , 61 ]. BPO, a major initiator for self-curing acrylic resin, is broken down during polymerization to release radicals that injure surrounding cells [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments using keratinocytes and the derivatives of epithelial cells were desired. Future studies other than those already mentioned may include the development of materials with high cytocompatibility properties (i.e., N-acetyl cysteine and tri-n-butyl borane) to improve reduction–oxidation systems and reduce radical production [ 53 , 61 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary human oral fibroblasts (ScienCell Research Laboratories, Carlsbad, CA, USA) were cultured, as reported elsewhere [94][95][96], in a company-recommended medium supplemented with 5% fetal bovine serum (FBS), 1% fibroblast growth supplement-2 (ScienCell Research Laboratories), and 1% penicillin/streptomycin solution. At 80% confluence, the cells were detached using 0.05% trypsin-EDTA solution and seeded onto each test zirconia specimen placed in a well (20 mm diameter) of 12-well culture plates at a density of 4 × 10 4 cells/well.…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, it was reported that different amino acids are utilized to fabricate chemical caries removal products, such as Caridex and Carisolv [81]. Another application of amino acids was investigated, as it has been reported that novel dental restorative materials and cements were made by incorporating different amino acids [82][83][84][85]. Zilm et al showed that D-amino acids can reduce the bacterial biofilm of Enterococcus faecalis in the presence of other antibacterial agents in an in vitro model [86].…”
Section: Potential Uses Of Ad (Baobab) Extracts In Dentistry Accordin...mentioning
confidence: 99%